Successful treatment of etanercept- and adalimumab-resistant pyoderma gangrenosum with spesolimab, moderate-dose corticosteroids, and minocycline - Hanlin Zhang; Chao Wu; Hongzhong Jin (Journal of Dermatological Treatment)
Purpose Pyoderma gangrenosum (PG) is a rare, neutrophilic dermatosis characterized by rapidly developing, painful ulcers. This study explores the potential of spesolimab, an anti-IL-36R antibody, as a therapeutic option for refractory PG.Materials and methods We report a case of a 48-year-old male with refractory PG who failed to respond to etanercept and adalimumab. Upon admission, the patient presented with extensive, painful ulcerations on the trunk and extremities. He was started on oral methylprednisolone (32 mg/day) and minocycline (50 mg twice daily). After a week, minimal improvement was observed. After reviewing the screening results and discussing treatment options, the patient received two doses of spesolimab (900 mg intravenously) administered two weeks apart.Results Marked clinical improvement was observed after spesolimab initiation. Complete ulcer healing was achieved within six weeks of starting spesolimab, with no adverse effects reported.Conclusions This case demonstrates the potential efficacy of spesolimab for treating refractory PG, particularly in patients unresponsive to TNF-α inhibitors. Despite the added complexity of the patient’s underlying HBV infection and elevated M-protein, no HBV reactivation or other hematologic complications occurred. Further studies are needed to validate its role in managing PG and other neutrophilic dermatoses.